SPEECH PERCEPTION BUNYI KONSONAN PADA PEMBELAJAR BAHASA JEPANG BERBAHASA IBU JAWA MANCANEGARI - Rizki Avrilian Nur Dayanto; Roni Roni; Urip Zaenal Fanani (UNES Law Review, 2023)
Problems with pronunciation and accent in Japanese language learners often occur because learners have different mother tongues. This study aims to describe how the form of perception of consonant utterances in Japanese language learners whose native Javanese language is foreign when compared to native Japanese. The consonants that will be test are Japanese plosives and fricatives. The method used in this research is descriptive qualitative where the researcher will describe the results of data analysis and explain facts about perceptions of mother tongue speech, which interfere with foreign language learners, especially Japanese. The analysis was carried out based on the recording when testing words containing plosive and fricative consonants. Based on the results of the analyze in this study, it can be interpreted that Japanese language learners whose mother tongue is Javanese Mancanegari have differences from native Japanese speakers, both in terms of the frequency of the spoken consonants and in terms of the pitch-accent waves